Analisis Taksonomi Bloom Dalam Mengidentifikasi Tingkat Kesulitan Pertanyaan Soal Dalam Mata Pelajaran Matematika Di Sekolah Dasar - Ina Magdalena; Aan Nurchayati; Astika Nurhayati Saputri; Nur Zakia Amanda; Naufal Habibie; Sashy Noviana Waluyo; Diana Khoirun Nisa (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to analyze the use of Bloom's Taxonomy in identifying the difficulty level of questions in mathematics in elementary schools. Bloom's taxonomy is a classification framework used to classify learning objectives into six different levels, namely knowledge, understanding, application, analysis, synthesis, and evaluation. The research subjects were 15 students in class V at SDN Karet 2, Tangerang Regency. The research method used was content analysis, in which questions in mathematics textbooks for elementary schools were analyzed based on Bloom's Taxonomy categories. The data collected included the difficulty level of the questions based on Bloom's taxonomy and the distribution of the difficulty levels of the questions in mathematics textbooks. The results showed that the level of difficulty of the questions in mathematics in elementary schools varied and could be classified based on Bloom's taxonomy. Most of the items focus on levels of knowledge and understanding, with a few items testing students' abilities to apply, analyze, synthesize, and evaluate mathematical concepts. This shows that there is a tendency to emphasize understanding concepts rather than applying concepts in learning mathematics in elementary schools.